The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.ppnp.2006.09.001
|View full text |Cite
|
Sign up to set email alerts
|

On the running coupling constant in QCD

Abstract: We try to review the main current ideas and points of view on the running coupling constant in QCD. We begin by recalling briefly the classic analysis based on the Renormalization Group Equations with some emphasis on the exact solutions for a given number of loops, in comparison with the usual approximate expressions. We give particular attention to the problem of eliminating the unphysical Landau singularities, and of defining a coupling that remains significant at the infrared scales. We consider various pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
234
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(246 citation statements)
references
References 222 publications
(373 reference statements)
9
234
0
Order By: Relevance
“…The running coupling must go to zero like the fourth power of momentum being this in agreement with lattice computations as shown by Boucaud et al [17] but as also seen from experiments as shown by Prosperi et al [18,19,20]. These latter results on the running coupling give a strong clue that Yang-Mills theory is trivial as happens for the scalar field theory.…”
supporting
confidence: 85%
“…The running coupling must go to zero like the fourth power of momentum being this in agreement with lattice computations as shown by Boucaud et al [17] but as also seen from experiments as shown by Prosperi et al [18,19,20]. These latter results on the running coupling give a strong clue that Yang-Mills theory is trivial as happens for the scalar field theory.…”
supporting
confidence: 85%
“…[115][116][117], this prescription yields a misleading result, which differs from the proper one (10) even in the deep ultraviolet asymptotic, see also Refs. [42,118,119] as well as [31] and the references therein.…”
Section: R-ratio Of Electron-positron Annihilation Into Hadronsmentioning
confidence: 99%
“…(f) Finally, it is important to note that the Laplacian sun rule (54) is based on the Borel transform for the global duality relation (52), not based on the so-called strict local duality…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The expressions for the three-loop running coupling constant α s (Q 2 ) with three massless flavors (N f = 3) at renormalization scale µ [52] …”
Section: Numerical Analysismentioning
confidence: 99%